Energetic state during learning affects foraging choices in starlings - Marsh, B; Schuck-Paim, C; Kacelnik, A (2004)
We investigated the influence of energetic state at the time of acquaintance with a new food source on preference for that source on later encounters, using wild-caught European starlings as subjects. Twelve birds learned to obtain food rewards by pecking at either of two keys identified by color. The keys were encountered in different sessions, while the subjects were food deprived or prefed. Food rewards from both sources were always identical. After an equal number of reinforced trials with each source, the birds were presented with choices between them. The birds significantly preferred the source that had previously delivered food under higher deprivation. We relate these results to findings reported elsewhere of preferences for options previously associated with greater effort. We hypothesize that subjects may attribute value to an option according to the marginal fitness gain associated with this option in the past. Although this process may be adaptive under many circumstances, it violates the assumptions of normative models of choice that imply mechanisms of valuation sensitive to the absolute properties of a payoff or to expected absolute changes in state.